Respiratory sequelae and lung function after whooping cough in infancy. Issue 6 (June 1990) - Krantz, I; Bjure, J; Claesson, I; Eriksson, B; Sixt, R; Trollfors, B
Abstract : The lung function of 31 children, aged 6-13 years, who had whooping cough as infants and 32 control children matched for age, sex, and residence area were compared in a community based cohort study. Family history of obstructive airway disease, smoking habits in the family, atopy, and other background factors examined were similar in the two groups. The ratios of recalled repeated acute respiratory infections did not differ among the groups. Children in the control group were slightly more involved in physical activities. History of obstructive airway disease, findings on chest radiography, and distribution of immunoglobulin concentrations, including IgE, did not differ significantly. Lung function before and after exercise and after inhalation of salbutamol were not different. No impairment of small airways was detected. Our data do not support the hypothesis that whooping cough in itself is a causal factor for later obstructive respiratory disease.